Novel 3-(1H-indol-3-yl)-2-[3-(4-methoxyphenyl)ureido]- propanamides as selective agonists of human formyl-peptide receptor 2; Bioorganic & Medicinal Chemistry; Vol. 23, Iss. 14 - Lacivita E. Enza; Schepetkin (Shchepyotkin) I. A. Igor Aleksandrovich; Madia L. Stama; Kirpotina L. N. Liliya Nikolaevna; Colabufo N. A. Nicola; Perrone R. Roberto; Khlebnikov A. I. Andrey Ivanovich; Quinn M. T. Mark; Leopoldo M. Marcello (2015, 2015)
Title screen